Association between dietary habits and changes in cardiometabolic risk factors in the patients with metabolic syndrome: a 10-year follow-up study - Sarebanhassanabadi, Mohammadtaghi; Mirhosseini, Seyed Jalil; Mirzaei, Masoud; Namayandeh, Seyedeh Mahdieh; Soltani, Mohammad Hossein; Pedarzadeh, Ali; Baramesipour, Zahra; Faraji, Reza; Ahmadi, Nastaran; Salehi-Abargouei, Amin (Progress in Nutrition, 2019)
Background: Dietary habits are important in managing the cardiometabolic risk factors. The present study aimed to investigate the association between dietary habits and changes in components of metabolic syndrome (MetS) and other cardiometabolic factors in a sample of the Iranian adult population who had MetS based on a 10-year follow-up study. Materials and Methods: In this cohort study, 1979 urban adults aged 20-74 years were selected using a cluster sampling method in the context of the Yazd Healthy Heart Project (YHHP) during 2005-2006 and the data on demographics, education, physical activity, smoking, economic status, and dietary habits were collected. Biochemical tests, anthropometric and blood pressure measurements were also conducted. The same data were also collected during 2015-2016 for participants who had MetS at the first phase of the study. Results: Our analysis revealed that consumption of high-fat dairy significantly increased fasting blood glucose levels, and the participants who regularly consumed fast foods had a significantly higher waist circumference before and after adjustment for age and sex. However, the association disappeared in fully adjusted model in total population, yet, it remained significant only in males after subgroup analysis for fast food consumption (P